(untitled) (Research, Society and Development, 2022)
Introduction: With population aging, we have an increase in neurodegenerative conditions, including dementia syndromes. It is essential that health services are able to receive this demand, especially in Primary Health Care, for better monitoring of the elderly. Objective: to know the difficulties faced by doctors of the Family Health Strategy in the city of São Caetano do Sul in the care of patients with dementia. Method: this is a cross-sectional, quantitative, descriptive, exploratory approach, with a convenience sample, not probabilistic. The Brazilian version, validated for physicians, of the instrument “Atenció Sanitària de Les Demències: la visió de L’Atenció Primarià” was used. Results: 100% of the doctors of the Family Health Strategy in the municipality of São Caetano do Sul were evaluated. Regarding the care provided in Primary Health Care, 82.6% of the physicians evaluated reported that more than 25% of the patients seen were elderly. Most participants (64.3%) indicated that the greatest difficulty in identifying a case of dementia was the differentiation of signs and symptoms of dementia from geriatric depression. Another challenge observed by 46.4% of physicians was the differentiation of signs and symptoms of dementia from the physiological process of aging, senescence. Among the main signs and symptoms that lead to suspect the diagnosis of dementia, 46.4% of physicians pointed to cognitive impairment with memory alterations, 28.6% reported that the impairment of the ability to perform activities of daily living would be the first signs and symptoms and 21.4% reported that the presence of psychological and behavioral symptoms is what would most lead to suspicion of the diagnosis. Final Considerations: It was observed that physicians had difficulty in evaluating patients with cognitive complaints in relation to screening for reversible dementias and investigating differential diagnoses with common aging and mood disorders, for example. It is essential to train the studied group to improve the quality of care for the elderly.